Challenges of Ending the Rwandan Refugee Problem in Uganda; The relationship between the Old Case Loads and New Case Loads - Justus, Asasira; Winfred, Aliguma (International Journal of Social Work, 2022)
Uganda is home to over 1 million refugees and asylum seekers. The origin of refugees in Uganda is an unending crisis in the neighboring countries. Rwanda poses a big threat of ending the refugee problem as the host country has accommodated these refugees for over decades with no hopes to return. The two strands (old and new cases loads) make repatriation challenging due to divergent views and attitudes. The paper examines the relationship between the two strands of Rwandan refugees living in Nakivale settlement. Another niche in this paper is focused on how these refugees live with the host communities of Ugandan origin living around the settlement and answers partly why voluntary repatriation has not been realized among Rwandan refugees living in Uganda.
Keywords: Old Case Loads; Rwandan Refugee; Uganda